Simultaneous degradation of chlorpyrifos and profenofos in soils at sublethal concentrations in presence of Eisenia foetida and a native bacterial consortium - Elvis G. Gonzales-Condori; Giancarlo Avalos-López; Yusmil Vargas-Alarcón; Jeaneth M. Medina-Pérez; José A. Villanueva-Salas; Gabriela Briceño (Environmental Advances, 2024)
The use of organophosphates (OPPs) in agriculture is an environmental problem due to their persistence in the environment, affecting non-target species, including human beings. For this reason, this study evaluated the degradation of chlorpyrifos (CPF) and profenofos (PFF) simultaneously in soils at sublethal concentrations in the presence of Eisenia foetida (EF) and a native bacterial consortium (NBC). For this, we first studied the avoidance behavior of EF to soils contaminated with CPF and PFF by calculating the percentage avoidance response (AR%), finding that EF presents an avoidance behavior to soils contaminated with CPF (6.45 to 65.5 mg/kg) and PFF (2.26 to 112.95 mg/kg) and their mixture, giving values of AR% (+). EF did not show avoidance behavior with AR% (-) values when melon rinds were added as substrate making it feasible to study the degradation of CPF and PFF at concentrations of 65.5 mg/kg and 112.95 mg/kg. EF and NBC showed synergism in degradation, reducing the half-life time from 70 days (CPF) and 50 days (PFF) to 15 days in both cases, with degradation percentages at 28 days of 73.75% for CPF and 71.73% for PFF, with pH being the determining factor in degradation, favoring degradation at pH higher than 7. The study was scaled to real agricultural soils with concentrations of 0.801 and 0.592 mg/kg CPF and PFF, respectively. These concentrations represented an ecological risk with risk quotient values of RQ>1. After the application of EF and NBC, both OPPs were eliminated to non-detectable concentrations. It has been demonstrated that the application of EF and NBC is an effective alternative to be applied in agricultural soils contaminated with OPPs, which would reduce the negative impacts of these toxics on the environment and human beings.